Use of natural vegetable oils as alternative dielectric transformer coolants - S. M., Bashi; U. U, Abdullahi; Robia, Yunus; Amir, Nordin (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/